(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
Through my work I am showing the difficulties of cooperative learning in the opinion of Serbian teachers. During my reaserch, I examined the difficulties caused by the small-scale application of cooperative learning in teaching mathematics. A total of 257 teachers from different areas of Serbia participated in the research. The results show that preparation for cooperative learning has been a difficult and time consuming task for the teachers and that it is difficult to assess students individual performance and activity in this mode of learning. Among school conditions teachers emphasize the classroom layout as the biggest obstacle.